PTGDR expression is upregulated through retinoic acid receptors (RAR) mechanism in allergy - García-Sánchez, Asunción (PLoS One, 2019)
Functional studies suggest that promoter polymorphisms of the Prostaglandin D Receptor (PTGDR) gene can be involved in asthma. All-trans Retinoic acid (ATRA) has also been linked to allergic diseases. We have previously described the PTGDR promoter activation mediated by ATRA through response elements (RARE) at position -549T> C. In this study we aimed to analyze the effect of retinoic acid (RA) on the expression of PTGDR, the production of cytokines as well as to evaluate the binding of RA receptors to RA-Response Elements (RARE) sequences. A549 cells were transfected with vectors carrying different PTGDR haplotypes and treated with all-Trans Retinoic Acid (ATRA). PTGDR expression was measured by qPCR. Chromatin Immunoprecipitation assays (ChIP) were performed in ATRA stimulated KU812 cells and in PBMCs of patients carrying CTCT, CCCC or CCCT haplotypes. In addition, a broad panel of cytokines was analyzed by cytometric bead assay in A549 cells. The expression of PTGDR increased in A549 cells transfected with PTGDR-variants. The CCCC haplotype showed a significantly higher expression compared with CTCT. However, we found that RA up-regulated PTGDR expression through RARα mainly in the CTCT variant. Experiments on PBMCs from allergic patients carrying the -549T and -549C variant of the PTGDR promoter after ATRA and RAR antagonist administration confirmed the modulation of PTGDR by ATRA. The cytokine analysis showed that IL4 and IL6 levels were significantly increased in A549 cells transfected with PTGDR. In addition, ATRA treatment decreased the levels of IL4, IL6 and TNFα in A549 cells, whereas it increased IL4 and TNFα levels in PTGDR-transfected cells. We observed genetic differences in the regulation of PTGDR by ATRA that could contribute to the phenotypic differences observed in allergic patients. Our findings showed that RAR modulation by PTGDR might have an impact on Th2 responses, suggesting that RAR could be a potential therapeutic target in allergic inflammation.